PENDIDIKAN KARAKTER MELALUI PEMBIASAAN RUTIN UNTUK MENANAMKAN NILAI - NILAI PENDIDIKAN ISLAM PADA SISWA SD/MI - Ninik Hidayati; Nurul Hakim; M. Zakki Sulton (Program Studi PGMI Fakultas Tarbiyah Institut Agama Islam Nahdlatul Ulama Tuban, 2020)
Islamic Education Values ​​through the habituation program in SD / MI. The theories used as a foundation in this research include the theory of character education, routine habituation, and the values ​​of Islamic education. Based on the background of the problem, this research is expected to provide answers to the problem formulation (1). How is the implementation of character education through routine habituation to instill the values ​​of Islamic education in SD / MI students?, (2). How are the effectiveness and benefits of implementing routine habituation to instill the values ​​of Islamic education in SD / MI students? Based on the formulation of the problem, this study aims to (1). To find out the implementation of character education through routine habituation to instill the values ​​of Islamic education in SD / MI students. (2). This is to determine the level of effectiveness and benefits of routine habituation to instill the values ​​of Islamic education in schools in SD / MI students.